2006
DOI: 10.1634/stemcells.2005-0191
|View full text |Cite
|
Sign up to set email alerts
|

Basic Fibroblast Growth Factor Controls Migration in Human Mesenchymal Stem Cells

Abstract: Little is known about the migration of mesenchymal stem cells (MSCs). Some therapeutic approaches had demonstrated that MSCs were able to regenerate injured tissues when applied from different sites of application. This implies that MSCs are not only able to migrate but also that the direction of migration is controlled. Factors that are involved in the control of the migration of MSCs are widely unknown. The migratory ability of isolated MSCs was tested in different conditions. The migratory capability was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
146
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(164 citation statements)
references
References 51 publications
(52 reference statements)
15
146
0
3
Order By: Relevance
“…We attempted to determine the optimal dose of bFGF-2 for periodontal regeneration in dogs from several previous reports. bFGF-2 had a dose-dependent effect on periodontal regeneration at a dose ranging from 0 to 0.16% per implant [3][4][5][6][7][8][9][10][11][12][13][14][15][26][27][28][29] . Hayashi et al reported that new bone formation was smaller in the 0.56% bFGF-2 (100 µg bFGF-2/3×3×2 mm gelatin hydrogel) implant compared to the 0.056% bFGF-2 (10 µg bFGF-2/3×3×2 mm gelatin hydrogel) implant; however, there were no significant differences between them 29) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We attempted to determine the optimal dose of bFGF-2 for periodontal regeneration in dogs from several previous reports. bFGF-2 had a dose-dependent effect on periodontal regeneration at a dose ranging from 0 to 0.16% per implant [3][4][5][6][7][8][9][10][11][12][13][14][15][26][27][28][29] . Hayashi et al reported that new bone formation was smaller in the 0.56% bFGF-2 (100 µg bFGF-2/3×3×2 mm gelatin hydrogel) implant compared to the 0.056% bFGF-2 (10 µg bFGF-2/3×3×2 mm gelatin hydrogel) implant; however, there were no significant differences between them 29) .…”
Section: Discussionmentioning
confidence: 99%
“…Basic fibroblast growth factor-2 (bFGF-2) is a heparinbinding growth factor that exhibits potent angiogenic activity and mitogenic ability in mesenchymal cells [1][2][3][4][5][6][7] and periodontal ligament cells [8][9][10][11] . Several studies have reported that bFGF-2 induces potent periodontal tissue regeneration along with new alveolar bone and cementum formation without aberrant healing such as root resorption and ankylosis in critical size defects of animal models [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…MSC demonstrate an increased migratory propensity in the presence of basic fibroblast growth factor through a phosphoinositide-3 kinase/AKT pathway downstream of the basic fibroblast growth factor receptor on the MSC. 51 Chemokine/cytokine secretion and the respective receptors found on MSC Monocyte-chemoattractant protein 1 (CCL2), a chemokine secreted by tumor cells, was shown to be a potent chemoattractant for MSC migration toward breast carcinomas. 52 However, prior studies show conflicting data on the migratory response to CCL2.…”
Section: Activation Of Msc With Proinflammatory Cytokines (That Is Tmentioning
confidence: 99%
“…Along with PDGF-BB and IGF-1, we investigated three additional factors: the basic fibroblast growth factor (bFGF), the stromal cell-derived factor 1a (SDF-1a), and the growth/differentiation factor 5 (GDF-5). The growth factor bFGF has shown the capacity to improve tenocyte proliferation and collagen synthesis, 22 MSC chemotaxis, 31 and the tenogenic differentiation of MSCs both in two-dimensional (2D) 32 and 3D 33 culture systems. SDF-1a has been implicated as a potent chemoattractant of MSCs during wound healing, 29,34 but recently has shown the ability to improve ligament stem cell proliferation and migration 35 as well as functional tendon regeneration in a rat Achilles model.…”
Section: Introductionmentioning
confidence: 99%